A New Test Scheme for Process Variation-Induced Faults in Resistive RAMs - Haron, Nor Zaidi; Fauziyah , Salehuddin; Norsuhaidah , Arshad; Zahriladha , Zakaria (2013)
Resistive random access memory (RRAM) is vying to be one of the main universal memories for computing systems. Nonetheless, due to infancy knowledge and technology to fabrication RRAM, this emerging memory technology is expected to be impacted by processvariation-induced faults. Due to their varying behavior, processvariation-inducedfaults are problematic to be detected using existing test approach that is solely based on the March test concept. This manuscript presents a new test scheme based on the combination of the Design-for-Testability (DfT) concept with the March test concept to detect such faults. Unlike the conventional DfT that asserts a single, fixed write voltage during testing, the proposed test scheme asserts multiple voltage levels that can be digitally adjusted. Simulation results using Verilog-AMS and HSPICE tools show that the process variation-induced faults can be detected with minor circuit modification. In addition, as the proposed test approaches are programmable, the proposed test scheme alleviates the redesign phase and in turn accelerates time-to-market.